(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2022)
The experimental data for (relative permittivities) and n (refractive indices), were measured for mixtures of 2-butanone (BN) (CH3COCH2CH3) with dichloromethane (22), 1,2-dichIoroethane (CH2Cl.CH2Cl) and tetrachloroethene (CCl2CCl2) at the temperature 308.15 K. The values of ∆ which represent the departures of the for the mixtures from the quantities occuring from the law achieved from mole fraction mixture, have been obtained. Calculated values of ∆ shows positive sign for BN with CH2Cl2 and CH2Cl.CH2Cl, whereas it is negative in the case of BN with CCl2CCl2. With the help of the values of and n, the Kirkwood correlation parameter, g, have been calculated for mixtures of BN with CH2Cl2 and CH2Cl.CH2Cl. The values of g indicate that BN forms intermolecular complexes with these compounds. The Equilibrium constant Kf, for the creation of complexes (1:1) of BN with CH2Cl.CH2Cl and CH2Cl2, have also been obtained with the experimental data for .